Opportunities and Benefits Implementation Business Intelligence Application on Health Center - Hady Pranoto (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The health center has the task of providing health services to the community, to be able to win the competition among the existing health centers; a health center should have a good operating system, a computerized operating system to improve services in the field of administration. However, providing a computerized system is not enough, many other health centers or competitors also use a computerized system. Unfortunately, health centers in Indonesia have not yet implemented business intelligence application. There are many public and private health centers do not apply automated operational system. A study of the literature is conducted to find evidence of the application of BI, and any sector of the BI can be applied. Many sectors in health services where BI can be applied to improve the productivity quality of service and competitiveness in this era of globalization.